Implementation of Gauss Elimination Method on Electrical Circuits Using Python - Karo Karo, Ichwanul Muslim; Karo Karo, Justaman Arifin; Yunianto; Hariyanto; Falah, Miftahul; Ginting, Manan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Problem solving in engineering, science and other disciplines often requires complex and in-depth analysis. A problem that requires effort is determining the value of electric current in a circuit. Generally, the determination of the current value in a circuit with the calculation of Kirchoff's theorem. This research presents an alternative approach to determine the value of electric current in a circuit by combining the Gauss Elimination method and Kirchoff's theorem. The determining process support by Python. This method is effective in finding unknown values in a system of linear equations through matrix operations. A deep understanding of currents in electrical circuits is essential in the design, analysis, and maintenance of electrical systems. The application of the Gauss Elimination Method becomes important in determining the value of current in complicated electrical circuits. The Gauss Elimination Method is able to solve electrical circuit problems using matrix principles to achieve accurate and relevant solutions